Can spatial and temporal food variability explain the winter foraging movements of a threatened saltmarsh insectivore?. (1st September 2014) - Lindsay, Kurtis J.; Allen, Andrew P.; Major, Richard E.
Abstract: The white‐fronted chat ( E pthianura albifrons ) is a small, insectivorous passerine that is threatened with extinction in the north‐eastern part of its range, partially due to loss and degradation of its saltmarsh habitat. Food availability is a potential limiting factor for the disjunct populations that survive in saltmarsh refugia, surrounded by urbanized land, because the anthropogenic matrix reduces the capacity of birds to commute to alternative grassland habitat to exploit temporary insect outbreaks. This limitation is likely to be exacerbated during the winter months when local arthropod abundance in saltmarsh is reduced. This study measured temporal and spatial variation in the abundance of saltmarsh arthropods to determine whether patch switching by foraging flocks can be explained by variation in food availability. Arthropods in the size range known to be important in the diet of white‐fronted chats were vacuum‐sampled from six patches within a continuous area of S arcocornia ‐dominated saltmarsh over a four‐month period. The location of foraging birds was recorded during the same period. Despite superficial similarity in vegetation composition and structure, there was significant variation in arthropod biomass among sites through time, such that the patches with the highest food abundance changed from month to month. There was little evidence, however, to suggest that white‐fronted chats foraged in saltmarsh patches with the highest overall food abundance. During the course of the study, birds were discovered flying 2 km from the saltmarsh to a development site where they foraged in weedy grassland. Arthropod samples collected from this site contained an extremely high abundance of Hemiptera and Neuroptera larvae, supporting previous research indicating that white‐fronted chats forage on irruptions of particular arthropod taxa. These findings indicate that food abundance is unlikely to be the main determinant of foraging site selection within saltmarsh, but highlights the potential importance of alternative foraging habitat types for this species.